A dynamic context of behavioural strategy: managerial cognitive capabilities and organizational adaptive performance - Piórkowska, Katarzyna (Management Sciences, 2017)
The prior research has emphasized the importance of either individuals to organizational performance or of managerial cognition to strategic change and action and provided support for the salient role of managerial cognition in developing managerial capabilities and behaviour. Nevertheless, given that managerial perceptions may vary across industry contexts and that high and low velocity industry pose different cognitive challenges to managers, there is no prior research investigating the associations between managerial cognitive and adaptive capabilities, the individual propensity to adapt, and organizational adaptive performance in a high velocity industry, only some research has explored how individual characteristics affect the ability to develop adaptive capabilities. Hence the aim of the paper is to present a theoretical and methodological proposition exploiting a cognitive approach and a microfoundations perspective in strategic management, aiming to examine the interdependencies between managerial cognitive capabilities ,adaptive capabilities, and organizational adaptive performance as well as explore the moderators and/or mediators of that relationship. The method used is the literature review. The main findings constitute the propositions resulting from a developed conceptual framework
Nauki o Zarządzaniu = Management Sciences, 2017, Nr 1 (30), s. 24-30
Keywords: behavioural strategy; micro-foundations; adaptive performance; strategia behawioralna; mikrofundamenty; organizacyjna adaptacyjność